DFT, experimental and optimization studies on the corrosion inhibition of aluminium in H2SO4 with danacid as inhibitor - O.D. Onukwuli; I.A. Nnanwube; F.O. Ochili; M. Omotioma (Results in Engineering)
The inhibitive action of expired danacid toward the dissolution of aluminium in 1 M H2SO4 was examined in this study via gravimetric, electrochemical, and theoretical method via density functional theory (DFT) in addition to studying the surface morphology and functional groups with scanning electron microscope (SEM) and Fourier transform infrared spectroscopy (FTIR). Optimization of inhibition parameters was performed with response surface methodology (RSM). FTIR result indicates the presence of heteroatoms in the inhibitor while further study by gas chromatography mass spectrometry (GC-MS) revealed the presence of octadecane, carbonic acid, eicosyl vinyl ester, dotriacontane, 1-chloro- Hexadecane, 1-chloro-octadecane, 1-fluoro-Tetradecane, n-hexadecanoic acid, pentafluoropropionic acid, tetradecyl ester, linoelaidic acid, among others. The inhibition efficiency of expired danacid increased with increase in danacid's concentration and reduced with rise in temperature. Potentiodynamic polarization (PDP) result portrayed the expired danacid as a mixed-type inhibitor (M-TI) with the highest inhibition efficiency (IE) of 94.06 % while RSM optimization gave an IE of 94.24 %. DFT analysis revealed further parameters that support the inhibitory action of danacid. Adsorption studies showed that Langmuir isotherm gave the best fit to the experimental data. Artificial neural network (ANN) modeling further improved on the RSM predicted results. The experimental, electrochemical and optimization results show consistency with each other.